Effect of Microwave Radiation on the Floatation of Copper Sulfide Ores - Kaya, Erol (Asian Journal of Chemistry, 2010)
The objective of this study is to evaluate the floatation behaviour of microwave pre-treated 2 sulfide copper ores containing different mineralogy. Each ore was subjected to microwave radiation for varying time periods before grinding and subsequent floatation testing. The changes in floatation recoveries and grades with the microwave exposure time were quantified by batch type laboratory tests. The results of the floatation tests indicated essentially the same recoveries at low tempera-tures for both the microwave treated copper ores compared to untreated samples. On the other hand, the results showed that high microwave radiation temperatures were detrimental to floatation recovery for both the copper ores due possibly to microwave energy induced oxidation of minerals at relatively high temperatures. The existence of significant oxidized areas on high-grade chalcopyrite particles were shown when heated with microwaves. Differing ore mineralogy has been shown to affect the floatability of the ores treated with microwaves.